Hematopoietic stem cell transplantation alters susceptibility to pulmonary hypertension in Bmpr2-deficient mice. (September 2018) - Crosby, Alexi; Toshner, Mark R.; Southwood, Mark R.; Soon, Elaine; Dunmore, Benjamin J.; Groves, Emily; Moore, Stephen; Wright, Penny; Ottersbach, Katrin; Bennett, Cavan; Guerrero, Jose; Ghevaert, Cedric; et al.
Increasing evidence suggests that patients with pulmonary arterial hypertension (PAH) demonstrate abnormalities in the bone marrow (BM) and hematopoietic progenitor cells. In addition, PAH is associated with myeloproliferative diseases. We have previously demonstrated that low-dose lipopolysaccharide (LPS) is a potent stimulus for the development of PAH in the context of a genetic PAH mouse model of BMPR2 dysfunction. We hypothesized that the hematopoietic progenitor cells might be driving disease in this model. To test this hypothesis, we performed adoptive transfer of BM between wild-type (Ctrl) and heterozygous Bmpr2 null (Mut) mice. Sixteen weeks after BM reconstitution, mice were exposed to low-dose chronic LPS (0.5 mg/kg three times a week for six weeks). Mice underwent right heart catheterization and tissues were removed for histology. After chronic LPS dosing, Ctrl mice in receipt of Mut BM developed PAH, whereas Mut mice receiving Ctrl BM were protected from PAH. BM histology demonstrated an increase in megakaryocytes and there was an increase in circulating platelets in Ctrl mice receiving Mut BM. These findings demonstrate that the hematopoietic stem cell compartment is involved in the susceptibility to PAH in the Mut mouse. The results raise the possibility that hematopoietic stem cell transplantation might be a potential treatment strategy in genetic forms of PAH.